Video-based training of situation awareness enhances minimally invasive surgical performance: a randomized controlled trial: dynamic manuscript - Kowalewski, Karl-Friedrich; Luyken, Laura; Benner, Laura; Schmidt, Mona Wanda; Ali, Seher; Fan, Carolyn; Köppinger, Karl Felix; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2023)
Many training curricula were introduced to deal with the challenges that minimally invasive surgery (MIS) presents to the surgeon. Situational awareness (SA) is the ability to process information effectively. It depends on general cognitive abilities and can be divided into three steps: perceiving cues, linking cues to knowledge and understanding their relevance, and predicting possible outcomes. Good SA is crucial to predict and avoid complications and respond efficiently. This study aimed to introduce the concept of SA into laparoscopic training.
Online veröffentlicht: 14. April 2023
Gesehen am 15.07.2024